Hollow engineering of HCNs@CoFe2Se4-QDs with quantum dots toward ultra-broadband electromagnetic wave absorption - Zizhuang He; Chenyu Wang; Ran Sun; Sihan Liu; Lianfei Ding; Tiande Gao; Panbo Liu (Journal of Advanced Ceramics)
Hollow engineering is considered to be an essential subfield in promoting electromagnetic (EM) wave absorption intensity and realizing lightweight characteristics. However, the enhancement of the effective absorption bandwidth (EAB) still faces considerable challenges. Herein, hollow carbon nanocages with CoFe2Se4 quantum dots (HCNs@CoFe2Se4-QDs) with superior EM wave absorption intensity and ultra broadband EAB are produced by using tightly arranged SiO2 spheres as hard-template materials. Specifically, the removal of SiO2 templates inevitably results in the formation of a hollow cavity, which is favorable for optimizing impedance matching and increasing the absorption intensity. In addition, the incorporation of selenium powder effectively increases the number of heterogeneous interfaces by forming CoFe2Se4 quantum dots (QDs) during the pyrolysis process, leading to strengthened interfacial polarization and ultra broadband EAB. As a result, superior EM wave attenuation with a minimum reflection loss (RL) of −67.6 dB and an EAB of 11.4 GHz is achieved with only a 20 wt% filler ratio. This design concept of hollow engineering with magnetic QDs provides inspiration for optimizing the EM wave absorption intensity and simultaneously promoting the absorption bandwidth.